The Quality of Cattle Manure Compost with Addition of Various Peatland Vegetation - Anjalani, Ria; Paulini; Ningsih, Ayu Kusuma (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
This study aimed to determine the quality of cattle manure compost with the addition of various peatland vegetation plants. The study used a Completely Randomized Design consisting of five treatments with four replications, namely P1 (Stenochlaena palustris), P2 (Dryopteris sp.), P3 (Hymenachne amplexicaulis), P4 (Eleocharis dulcis), and P5 (Imperata cylindrica). The observed parameters included the physical and chemical properties of compost. Data on physical properties were descriptively analyzed, while chemical properties were analyzed using analysis of variance followed by Duncan’s Multiple Range Test when significant differences were found among treatments. The results showed that composts P1 and P2 exhibited changes in color, smell, and texture. Compost P3 showed only a color change. Composts P4 and P5 showed changes in color and smell. Final compost temperature ranged from 28.50 to 28.88°C. The addition of peatland vegetation significantly affected pH, organic C, total N, and C/N ratio (P<0.01).